The Combination of Rice Water and BAP Enhances the Multiplication of Grammatophyllum speciosum - Innaka Ageng Rineksane; Siti Safitri Nafiah; Sukuriyati Susilo Dewi (Universitas Muhammadiyah Yogyakarta, 2018)
Grammatophyllum speciosum is the largest orchid species which lives epiphytically on the trees in the forest. The rate of natural propagation of Grammatophyllum speciosum is very slow. The objective of the research was to determine the effect and the best concentration of rice water and BAP for the multiplication of Grammatophyllum speciosum shoots. The research was a single factor experiment arranged in Completely Randomized Design with several types of multiplication media as treatments. The treatments were MS + 0.5 mg/l BAP, ½ MS + 25% rice water + 0.5 mg/l BAP, ½ MS + 50% rice water + 0.5 mg/l BAP, ½ MS + 75% rice water + 0.5 mg/l BAP, ½ MS + 100% rice water + 0.5 mg/l BAP, MS + 1 mg/l BAP, ½ MS + 25% rice water + 1 mg/l BAP, ½ MS + 50% rice water + 1 mg/l BAP, ½ MS + 75% rice water + 1 mg/l BAP, and ½ MS + 100% rice water + 1 mg/l BAP. Each treatment was replicated ten times. Variables observed in this study were survival rate, browning rate, contamination rate, the percentage of explants sprouting, the increase of shoot height, number of shoots and leaves, the percentage of rooted explants and the number of roots. The data were analyzed by using Analysis of Variance at α=5%. The results showed that various concentrations of rice water and BAP were able to multiply the shoots and affect the shoot growth and root length of Grammatophyllum speciosum. The combination of 75% rice water + 1 mg/l BAP on ½ MS medium was the best treatment for Grammatophyllum speciosum multiplication